Bacterial crack healing in metakaolin based geopolymer mortars - Polat, Berivan Yilmazer; Uysal, Mucteba (ELSEVIER, 2021)
Geopolymer mortars have emerged as an environmentally friendly binding alternative to conventional cement. However, the gaps in their structure and early cracks reduce their service life. There are various bacterial healing studies in the literature that have been conducted on cemented mortar cracks. Nevertheless, the present study focuses on the healing of metakaolin based geopolymer mortar cracks. For this purpose, mortars with different molarities were prepared with two different endospore forming methods that did not require encapsulation or mixed chemical processes for the bacterial crack repairs on the geopolymer mortars. These mortars were then left in different healing environments with crack damage. The samples were tested using physical, optical and internal structure analyses. As a result, the cracks were improved by reducing the amount of gaps in the samples. The results showed that it is possible to bacterially repair early cracks in new generation ceramic materials with alkali-activated mortars and reduce the amount of gaps.
Keywords: Geopolymer mortar; Bacterial self healing; Bioconcrete; Crack; COMPRESSIVE STRENGTH; CEMENT; PRECIPITATION; PERMEABILITY; RATIO; SLAG; Construction & Building Technology; Engineering